2021
DOI: 10.1021/acs.chemmater.1c02059
|View full text |Cite
|
Sign up to set email alerts
|

Role of Electronic Structure in Li Ordering and Chemical Strain in the Fast Charging Wadsley–Roth Phase PNb9O25

Abstract: Wadsley–Roth crystallographic shear phases are a family of transition-metal oxides that show tremendous promise as electrode materials in Li-ion batteries. Despite their ability to intercalate lithium at high rates, little is known about their structural, thermodynamic, and electronic properties as a function of Li concentration. In this study, we use first-principles statistical mechanics methods to explore the lithium-site preference, lithiation strain, and electronic structure of PNb9O25, a Wadsley–Roth pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(72 citation statements)
references
References 74 publications
5
63
0
Order By: Relevance
“…Subsequently, the Li + gradually fills the two window sites (W v and W h ). 105 In situ XRD analysis of PNb 9 O 25 during lithiation (Figure 8D) reveals three solid-solution regions (3.0-1.62, 1.54-1.11 V, and 1.08-1.0 V) and two two-phase regions (plateau at around 1.62 and 1.11 V) during the entire lithiation process. 106 Moreover, Preefer et al 107 found that an insulator-to-metal transition can occur during the lithiation process of PNb 9 O 25 , with the material remaining insulating at low levels of lithiation, owing to localization of the electron density, and showing metallic behavior after full lithiation.…”
Section: Other Nb-based Oxidesmentioning
confidence: 97%
See 2 more Smart Citations
“…Subsequently, the Li + gradually fills the two window sites (W v and W h ). 105 In situ XRD analysis of PNb 9 O 25 during lithiation (Figure 8D) reveals three solid-solution regions (3.0-1.62, 1.54-1.11 V, and 1.08-1.0 V) and two two-phase regions (plateau at around 1.62 and 1.11 V) during the entire lithiation process. 106 Moreover, Preefer et al 107 found that an insulator-to-metal transition can occur during the lithiation process of PNb 9 O 25 , with the material remaining insulating at low levels of lithiation, owing to localization of the electron density, and showing metallic behavior after full lithiation.…”
Section: Other Nb-based Oxidesmentioning
confidence: 97%
“…(C) Crystal structure of PNb 9 O 25 and different lithium sites in PNb 9 O 25 . Reproduced with permission from Saber et al 105 Copyright: 2021 American Chemical Society. (D) Operando XRD characterization and the evolution of lattice parameters for PNb 9 O 25 during the first cycle.…”
Section: Crystallographic Shear Structures Of Nb‐based Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other transition-metal oxides, such as PNb 9 O 25 , are also accompanied by a tetragonal distortion (from Jahn-Teller effect) of its lattices along the c−axis. These structural distortions coupled with the electronic structure of PNb 9 O 25 affects the ordered filling of multiple Li ions [13]. Overall, these abrupt crystallographic changes can induce significant misfit strains between neighboring lattices and collectively generate volume changes.…”
Section: Types Of Structural Transformationmentioning
confidence: 99%
“…For example, intercalating ions in LiCoO 2 (a commonly used cathode) preferentially diffuse parallel to the (001) crystallographic planes. This preferential diffusion constrains ion migration to specific crystallographic channels and thus limits rapid charge/discharge properties [13,14].…”
Section: Introductionmentioning
confidence: 99%